A multicenter, randomized, double‐blinded, placebo‐controlled phase III study of Clot Lysis Evaluation of Accelerated Resolution of Intraventricular Hemorrhage (CLEAR III). Issue 4 (28th August 2013) - Ziai, Wendy C.; Tuhrim, Stanley; Lane, Karen; McBee, Nichol; Lees, Kennedy; Dawson, Jesse; Butcher, Kenneth; Vespa, Paul; Wright, David W.; Keyl, Penelope M.; Mendelow, A. David; Kase, Carlos; et al.
<x xml:space="preserve">Abstract</x> Background In adults, intraventricular thrombolytic therapy with recombinant tissue plasminogen activator (rtPA) facilitates resolution of intraventricular haemorrhage (IVH), reduces intracranial pressure, decreases duration of cerebrospinal fluid diversion, and may ameliorate direct neural injury. We hypothesize that patients with small parenchymal haematoma volumes (<30 cc) and relatively large IVH causing acute obstructive hydrocephalus would have improved clinical outcomes when given injections of low‐dose rtPA to accelerate lysis and evacuation of IVH compared with placebo. Methods The Clot Lysis Evaluation of Accelerated Resolution of Intraventricular Hemorrhage III trial is an investigator‐initiated, phase III, randomized, multicenter, double‐blind, placebo‐controlled study comparing the use of external ventricular drainage (EVD) combined with intraventricular injection of rtPA to EVD plus intraventricular injection of normal saline (placebo) for the treatment of IVH. Patients with known symptom onset within 24 h of the computed tomography scan confirmed IVH and third or fourth ventricle obstruction, with or without supratentorial intracerebral haemorrhage volume <30 cc, who require EVD are screened with a computed tomography scan at least six hours after EVD placement and, if necessary, at consecutive 12‐h intervals until stabilization of any intracranial bleeding has been established. Patients who meet clinical and imaging criteria (no ongoing coagulopathy and no suspicion of aneurysm, arteriovenous malformation, or any other vascular anomaly) will be randomized to either intraventricular rtPA or placebo. Results The primary outcome measure is dichotomized modified Rankin Scale 0–3 vs. 4–6 at 180 days. Clinical secondary outcomes include additional modified Rankin Scale dichotomizations at 180 days (0–4 vs. 5–6), ordinal modified Rankin Scale (0–6), mortality and safety events at 30 days, mortality at 180 days, functional status measures, type and intensity of intensive care unit management, rate and extent of ventricular blood clot removal, and quality of life measures.